An Adenovirus‐Mimicking Photoactive Nanomachine Preferentially Invades and Destroys Cancer Cells through Hijacking Cellular Glucose Metabolism. (10th December 2021) - Zhang, Yu; Feng, Shujun; Hu, Getian; Fang, Tianliang; Xie, Deqiao; Lu, Qiangbing; Xu, Yurui; Shen, Lida; Ning, Xinghai
Abstract: Elevated glucose metabolism is an important hallmark of malignancy, and closely relates to cancer growth and progression, making it a promising target for cancer treatment. Herein, an adenovirus‐mimicking nanomachine (AMN) is developed for improving the management of malignancy, which has a unique core‐shell‐shell architecture consisting of gold nanorods (AuNR) and glucose oxidase (GOx) loaded zeolitic imidazolate framework‐8 (core) @ manganese dioxide mineralized albumin (BSA‐MnO2 ) (interior shell) @ RGD peptide‐functionalized PEG (exterior shell). AMN selectively invades tumor cells and triggers metabolic competition to limit nutrient availability, which not only directly eliminates cancer cells, but enhances cancer response to the treatment. It is identified that AMN exhibits good photothermal efficacy, which significantly enhances GOx activity to kill cancer cells. Meanwhile, AMN triggers MnO2 catalyzed oxygen generation, further improving GOx mediated starvation therapy, which greatly inhibits the expression of heat shock proteins and in turn enhances photothermal efficacy, resulting in synergistic anticancer effects. In vivo studies demonstrate that AMN selectively accumulates in the tumor and effectively eliminates the tumor without side‐effects. Notably, AMN exhibits trimodal imaging capability of photothermal, photoacoustic, and CT imaging, allowing for sensitively detecting tumors. Therefore, a promising anticancer strategy is provided by hijacking cellular glucose metabolism, which has great anticancer potential. Abstract : An adenovirus‐mimicking nanomedicine (AMN) is developed for improving the management of malignancy by reprogramming glucose metabolism, which is composed of gold nanorods and glucose oxidase loaded zeolitic imidazolate framework‐8 (core) @manganese dioxide mineralized albumin (interior shell) @RGD peptide‐functionalized PEG (exterior shell). AMN can not only especially invade cancer cells, but also effectively recover hypoxia and exhibit light‐enhanced metabolic competition, resulting in effectively suppressing tumors.